Kajian Awal Pengembangan E-Modul Augmented Reality untuk Era Society 5.0 - Kurnila, Nely; Harahap, Saima Putrini R; Kamil, Firmanilah (LPPM Press, 2025)
This study aims to develop an Augmented Reality (AR)-based electronic module for Indonesian language learning that aligns with the needs of vocational education students in the Society 5.0 era. The research employed a Multimedia Development Life Cycle (MDLC) approach, encompassing the stages of concept development, design, material collection, visual design creation, three-dimensional object development, and AR integration within a digital platform. Data were collected through document analysis (semester lesson plans and course materials), user needs observation, and validation by subject matter experts and media experts. Data analysis was conducted using quantitative descriptive techniques based on expert feasibility assessments. The results indicated that the e-module achieved an average score of 3.25 from subject matter experts and 3.17 from media experts on a four-point scale, placing it in the category of “feasible with revisions.” These expert evaluations served as the basis for module refinement, particularly in terms of visual presentation, clarity of instructions, and the responsiveness of AR objects. Thus, the developed e-module demonstrates potential to enhance student interactivity and independent learning. However, further refinement is required before the module is ready for large-scale field implementation.